Facebook Friends--Near and Far. - Miller, Nick; Clemens, Michelle; Gustafson, Kelsey; Brandt, Katie; Kirt, Megan (My University, 2009)
The research question under investigation is how has the use of Facebook strengthened the emotional relationships of those both geographically close and far away? 200 full time University of Wisconsin-Eau Claire Students were asked to take an online survey. 80 of them responded.
Color poster describing research conducted by Megan Kirt, Nick Miller, Katie Brandt, Kelsey Gustafson, and Michelle Clemens, advised by Jennifer Becker.
Keywords: Posters; Online social networks; Facebook (Internet resource); Social interaction--Computer network resources; Friendship--Effect of technological innovations on